The Impact of Concentrated Ownership Structure on Earning Quality with Political Connection As a Moderation - Y. Permatasari; T. I. M. Cahyadi; S. Trisnaningsih (Future Science)
This study aims to determine the effect of concentrated ownership structure on earnings quality with the political connection as a moderation variable. The variables used are concentrated ownership structure, earnings quality, political connection. The data used are secondary data and samples used are 229 manufacturing companies listed on the Indonesia Stock Exchange period 2012 to 2016. The data collected were analyzed using SPSS version 20 software tool with multiple linear regression method, linear regression, and Moderate Regression Analysis. Overall, this study proves that political connection can moderate the impact of concentrated ownership structure on earnings quality.